HOTTIP Mediated Therapy Resistance in Glioma Cells Involves Regulation of EMT-Related miR-10b - Li, Zhang; Li, Ming; Xia, Pengcheng; Lu, Zhiming (Frontiers in Oncology, 2022)
The advanced grade glioblastomas are characterized by dismal five-year survival rates and are associated with worse outcomes. Additionally, resistance to therapies is an additional burden responsible for glioma associated mortality. We studied the resistance against temozolomide (TMZ) as a surrogate to understand the mechanism of therapy resistance in glioma cancer cells. Screening of three glioma cells lines, A172, LN229 and SF268 revealed that SF268 glioma cells were particularly resistant to TMZ with the IC-50 of this cell line for TMZ ten times higher than for the other two cell lines. A role of lncRNAs in glioma progression has been identified in recent years and, therefore, we focused on lncRNAs for their role in regulating TMZ resistance in glioma cancer cells. lncRNA HOTTIP was found to be particularly elevated in SF268 cells and over-expression of HOTTIP in both A172 and LN229 remarkably increased their TMZ IC-50s, along with increased cell proliferation, migration, clonogenicity and markers of angiogenesis and metastasis. As a mechanism we observed increased expression of miRNA-10b and mesenchymal markers Zeb1/Zeb2 and reduced expression of E-cadherin in SF268 cells indicating a role of EMT in TMZ resistance. A172 and LN229 cells with overexpressed HOTTIP also had similarly induced EMT and the elevated miR-10b levels. Further, silencing of miR-10b in HOTTIP overexpressing cells as well as the SF268 cells reversed EMT with associated sensitization of all the tested cells to TMZ. Our results thus present a case for HOTTIP in native as well as acquired resistance of glioma cells against chemotherapy, with a key mechanistic role of EMT and the miR-10b. Thus, HOTTIP as well as miR-10b are critical targets for glioma therapy, and need to be tested further.